ETNO-STEM DALAM PEMBELAJARAN IPA : A SYSTEMATIC LITERATURE REVIEW - Minda Azhar; Fitri Arsih; Nurhasnah Nurhasnah; Yohandri Yohandri (Kwangsan: Jurnal Teknologi Pendidikan, 2022)
Ethno-STEM research is the latest research in Indonesia. This is motivated by the socio-cultural diversity that is owned by Indonesia. This research is a systematic literature study that identifies ethno-STEM research trends in science learning (science, physics, chemistry, and biology) at each level of education. Based on the data obtained, the trend of Ethno-STEM research is dominated by development research (4D, ADDIE, Bolg and Gall, and R&D). the trend of research topics is more related to the development of Ethno-STEM-based teaching materials in science learning. The variables that are widely measured are the increase in creative thinking skills, learning outcomes, and scientific knowledge AbstrakPenelitian etno-STEM merupakan penelitian terbaru di Indonesia. Hal ini dilatarbelakangi oleh keragamaan sosial budaya yang dimiliki oleh Indonesia. Penelitian ini merupakan penelitian studi literatur sistematis yang mengidentifikasi tren penelitian etno-STEM dalam pembelajaran IPA  (sains, fisika, kimia dan biologi) pada setiap tingkat pendidikan. Berdasarkan data yang diperoleh, trend penelitian Etno-STEM didominasi oleh penelitian pengembangan (4D, ADDIE, Bolg and Gall dan R&D). trend topik penelitian lebih banyak terkait dengan pengembangan bahan ajar berbasis Etno-STEM dalam pembeljaran IPA. Variabel yang banyak diukur adalah peningkatan kemampuan berfikir kreatif, hasil belajar dan pengetahuan sains.